Changes in Spirometry After Left Ventricular Assist Device Implantation. Issue 12 (21st May 2015) - Mohamedali, Burhan; Bhat, Geetha; Yost, Gardner; Tatooles, Antone
Abstract: Left ventricular assist devices (LVADs) are increasingly being used as life‐saving therapy in patients with end‐stage heart failure. The changes in spirometry following LVAD implantation and subsequent unloading of the left ventricle and pulmonary circulation are unknown. In this study, we explored long‐term changes in spirometry after LVAD placement. In this retrospective study, we compared baseline preoperative pulmonary function test (PFT) results to post‐LVAD spirometric measurements. Our results indicated that pulmonary function tests were significantly reduced after LVAD placement (forced expiratory volume in one second [FEV1 ]: 1.9 vs.1.7, P = 0.016; forced vital capacity [FVC]: 2.61 vs. 2.38, P = 0.03; diffusing capacity of the lungs for carbon monoxide [DLCO]: 14.75 vs. 11.01, P = 0.01). Subgroup analysis revealed greater impairment in lung function in patients receiving HeartMate II (Thoratec, Pleasanton, CA, USA) LVADs compared with those receiving HeartWare (HeartWare, Framingham, MA, USA) devices. These unexpected findings may result from restriction of left anterior hemi‐diaphragm; however, further prospective studies to validate our findings are warranted.